Nrl knockdown by AAV-delivered CRISPR/Cas9 prevents retinal degeneration in mice - Yu, Wenhan; Mookherjee, Suddhasil; Chaitankar, Vijender; Hiriyanna, Suja; Kim, Jung-Woong; Brooks, Matthew; Ataeijannati, Yasaman; Sun, Xun; Dong, Lijin; Li, Tiansen; Swaroop, Anand; Wu, Zhijian (Nature communications, 2017)
In retinitis pigmentosa, loss of cone photoreceptors leads to blindness, and preservation of cone function is a major therapeutic goal. However, cone loss is thought to occur as a secondary event resulting from degeneration of rod photoreceptors. Here we report a genome editing approach in which adeno-associated virus (AAV)-mediated CRISPR/Cas9 delivery to postmitotic photoreceptors is used to target the Nrl gene, encoding for Neural retina-specific leucine zipper protein, a rod fate determinant during photoreceptor development. Following Nrl disruption, rods gain partial features of cones and present with improved survival in the presence of mutations in rod-specific genes, consequently preventing secondary cone degeneration. In three different mouse models of retinal degeneration, the treatment substantially improves rod survival and preserves cone function. Our data suggest that CRISPR/Cas9-mediated NRL disruption in rods may be a promising treatment option for patients with retinitis pigmentosa. Retinitis pigmentosa is mainly caused by mutations that initially affect survival of rod photoreceptors, leading to secondary loss of cones. Here the authors use gene editing to prevent rod degeneration, leading to survival of cones and improved vision in mice.